The relationship marketing in the process of customer loyalty. Case large construction of Manizales - María Cristina Torres Camacho (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This paper is based on the model Lindgreen (2001), upholding the relationship marketing should be approached in three dimensions: objectives, definition of constructs and tools, which enable better customer management within organizations. The objective was to determine the characteristics of relationship marketing as a key factor in the process of Customer Loyalty in the big construction of Manizales Colombia. From a joint perspective, methodology relies on instruments and qualitative and quantitative analysis of court. The results tend to confirm that developers recognize the importance of Relational Marketing but not raised as a policy or have not defined in its strategic plan; additionally, expressed lack of strategies for customer retention, however, these remain loyal because the construction work on meeting your needs, based on trust, commitment and communication. To conclude, the faithful customers perceive that construction does not periodically evaluate their satisfaction with the purchased product, also claim that they show little interest in understanding the perception, make personal meetings, making constant communication through phone calls and meet their tastes and preferences.